THE RIGHT TO GOOD ADMINISTRATION – IS THE CONSTITUTIONAL REGULATION NECESSARY? - Oana ŞARAMET (Law Review  special issue, Decembre 2019, pp. 88-100, 2019)
The constitutional revision from 2003 enriched the patrimony of the fundamental rights and freedoms of Romanian citizens with three such rights and freedoms: the right to a healthy environment, economic freedom and access to culture. More than 16 years after this revision, but also as a member state of the European Union, we consider as an opportunity and necessity, at the same time, a new revision of our fundamental law, a consistent one at this moment, which should take into consideration the consecration of other rights, even by designing the necessary constitutional framework for ensuring and respecting a good administration. Analysing the constitutional provisions of other states, as well as those of the European level, the relevant doctrine and jurisprudence, using research methods such as multidisciplinary, comparative, sociological, empirical or systemic, it will be possible for us to conclude that good administration is one of those indefinite or determinable legal concepts. Being such a concept it is necessary to identify elements that allow us to configure it, elements that we should find in a unitary text in an article of our fundamental law, and through which the right to good administration would be enshrined. Therefore, we appreciate that in a state where the public administration, exercising of its functions and attributions, also had delicate moments in ensuring a good and efficient administration, the consecration of the right to good administration, by exhaustively capturing, as far as possible, the elements the definers of the concept of good administration, is a natural consequence of the constitutional recognition of the rule of law.
Keywords: Public Law; Administrative and Constitutional Law; right; good administration; constitutional provision